Conjugated linoleic acid: a potent fatty acid linked to animal and human health - Shokryazdan, Parisa; Rajion, Mohamed Ali; Goh, Yong Meng; Liang, Juan Boo; Bayramali, Mahdi Ebrahimi; Royan, Maryam; Sahebi, Mahbod; Azizi, Parisa; Abiri, Rambod; Jahromi, Mohammad Faseleh (Taylor & Francis, 2017)
Conjugated linoleic acid (CLA) is a mixture of isomers of linoleic acid (C18:2 n-6), which is mostly found in the ruminant meat and dairy products. The CLA is known to have many potential health benefits, and considered a potent powerful fatty acid, which is linked to animal and human health. The present work aims to discuss the source and production, mechanism of action, and effects of CLA on humans, poultry and ruminants by reviewing the recent studies carried out on CLA. Despite most of recent studies indicating beneficial effects of CLA on improving body weight control parameters, its effects on reducing risk factors of cardiovascular diseases (CVD), inflammation, blood glucose and insulin are still controversial, and need to be further studied in different hosts.